2015
DOI: 10.1002/chem.201500707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkyl Chain Length and Hydrogen Bonds on the Cooperative Self‐Assembly of 2‐Thienyl‐Type Diarylethenes at a Liquid/Highly Oriented Pyrolytic Graphite (HOPG) Interface

Abstract: An appropriate understanding of the process of self-assembly is of critical importance to tailor nanostructured order on 2D surfaces with functional molecules. Photochromic compounds are promising candidates for building blocks of advanced photoresponsive surfaces. To investigate the relationship between molecular structure and the mechanism of ordering formation, 2-thienyl-type diarylethenes with various lengths of alkyl side chains linked through an amide or ester group were synthesized. Their self-assemblie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 75 publications
2
38
0
Order By: Relevance
“…Similar phenomena have also been observed in arrays of other alkane derivatives, in which the alkyl chains take different angles to fulfill the formation of hydrogen bonds. [9,[33][34][35][36] In addition, the packing patterns of m-substituted 9-bpy and 14-bpy are similar to that of p-substituted bpy reported by De feyter et al, [26,27] except for only one type of adsorption structure was observed for 9-bpy and 14-bpy arrays. This may be due to the different structural symmetry of m-and p-substituted bpys.…”
Section: Packing Pattern Of 9-bpy On Hopgsupporting
confidence: 83%
“…Similar phenomena have also been observed in arrays of other alkane derivatives, in which the alkyl chains take different angles to fulfill the formation of hydrogen bonds. [9,[33][34][35][36] In addition, the packing patterns of m-substituted 9-bpy and 14-bpy are similar to that of p-substituted bpy reported by De feyter et al, [26,27] except for only one type of adsorption structure was observed for 9-bpy and 14-bpy arrays. This may be due to the different structural symmetry of m-and p-substituted bpys.…”
Section: Packing Pattern Of 9-bpy On Hopgsupporting
confidence: 83%
“…In this particular section of our present review, we focus on diarylethenes and how functionalities attached to their switching units affect the assembly/disassembly process in the solid/liquid interface. This section therefore aims to draw molecular design principles for surface assembly formation based on the particular geometry and photochemistry of diarylethenes on the solid/liquid interface, as such processes can give insight to surface‐molecule interactions …”
Section: Stm Of Diarylethenesmentioning
confidence: 99%
“…By looking at the concentration dependence of surface coverage, Matsuda et al . remarked that the nucleation process for 9 c assemblies was more thermodynamically favorable than that of the o form …”
Section: Stm Of Diarylethenesmentioning
confidence: 99%
See 2 more Smart Citations